Words Matter: Exposing the Camouflaged Violence of Hunting Rhetoric - Huse, Heidi (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
It’s easy to invoke words of kindness and peace; however, too often we do so without seriously considering exactly what we mean by what we say or what the implications might be of our words. In the contentious age in which we live, when virtually anyone can voice their views on TV or on the radio or Internet, we insist on the truthfulness of our personal standpoints—andthe erroneous thinking of those with other views—often with vitriol in our voices that contradicts our self-proclaimed peaceful intentions. I’m as guilty of such action as anyone else; however, despite my own hypocrisy, as a university writing teacher, I regularly challenge students to think about what they mean when they make public their professions of belief, endorsement, or disagreement in the classroom or in their writing.